microRNA-352 regulates collateral vessel growth induced by elevated fluid shear stress in the rat hind limb - Yinglu Guan (Nature Portfolio, 2017)
Abstract Although collateral vessel growth is distinctly enhanced by elevated fluid shear stress (FSS), the underlying regulatory mechanism of this process remains incompletely understood. Recent studies have shown that microRNAs (miRNAs) play a pivotal role in vascular development, homeostasis and a variety of diseases. Therefore, this study was designed to identify miRNAs involved in elevated FSS-induced collateral vessel growth in rat hind limbs. A side-to-side arteriovenous (AV) shunt was created between the distal stump of one of the bilaterally occluded femoral arteries and the accompanying vein. The miRNA array profile showed 94 differentially expressed miRNAs in FSS-stressed collaterals including miRNA-352 which was down-regulated. Infusion of antagomir-352 increased the number and proliferation of collateral vessels and promoted collateral flow restoration in a model of rat hind limb ligation. In cell culture studies, the miR-352 inhibitor increased endothelial proliferation, migration and tube formation. In addition, antagomir-352 up-regulated the expression of insulin-like growth factor II receptor (IGF2R), which may play a part in the complex pathway leading to arterial growth. We conclude that enhanced collateral vessel growth is controlled by miRNAs, among which miR-352 is a novel candidate that negatively regulates arteriogenesis, meriting additional studies to unravel the pathways leading to improved collateral circulation.